Digital Transformation in Public Administration: Towards Data-Driven Government - Dedy Suryadi; Ely Ibrahim (CV Edujavare Publishing, 2026)
Digital transformation has become a fundamental driver of change in public administration, enabling governments to transition toward data-driven governance models that enhance efficiency, transparency, accountability, and citizen-centered service delivery. This study aims to analyze the strategic role of digital transformation in building data-driven government and to examine the challenges and future directions associated with its implementation in the public sector. Using a qualitative literature review approach, the study synthesizes recent scholarly publications on digital governance, big data, artificial intelligence, and public sector innovation. The findings indicate that digital transformation facilitates evidence-based policymaking, improves public service quality, strengthens interagency collaboration, and promotes greater transparency through the effective use of data and digital technologies. However, the transition toward data-driven government is accompanied by significant challenges, including data quality issues, cybersecurity risks, privacy concerns, organizational resistance, digital skill shortages, ethical implications of artificial intelligence, and digital inequality among citizens. The study further highlights that emerging technologies such as artificial intelligence, blockchain, digital twins, and the Internet of Things are expected to play an increasingly important role in shaping the future of public administration. To maximize the benefits of digital transformation, governments must develop adaptive governance frameworks, invest in digital infrastructure and human capital, ensure ethical and transparent technology use, and promote inclusive digital participation. The study concludes that data-driven government represents a transformative governance paradigm capable of improving public sector performance and supporting sustainable public value creation in the digital era.